Peningkatan Aktivitas dan Hasil Belajar Siswa melalui Pendekatan Inkuiri pada Materi Sistem Perkembangbiakan Tumbuhan dan Hewan di Kelas IX MTsN 3 Aceh Timur - Hafnidar, Hafnidar (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
Education is part of national development which is directed at improving the dignity and quality of human resources. Quality Human Resources (HR) are very important in the development of a nation. The quality of a nation will be determined by its education, only quality human resources will be able to win the world labor market. This research is Classroom Action Research, aiming to determine the increase in student learning achievement through group investigation type cooperative learning on the material